Social hållbarhet i kollektivtrafikplanering : planeringsaktörers förhållningssätt och inkludering av sociala perspektiv. En studie av Metrobussystemet i storstadsområdet Göteborg - Haase, Sofia; Donalds, Emilia (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
The social sustainability sphere is often described as overshadowed by the economic and ecological sustainability spheres, but has recently gained increasingly more attention both in research and the practicality of planning. Transport and public transportation is an essential component in people’s abilities to appropriate their rights of participation in society and therefore in the process towards a social sustainable development. Generally, public transportation tends to be seen as something good. However, it could also be a causer of negative consequences such as creating barriers as well as act conducive to society’s increasing mobility gap, depending on how it is planned. Factors like gender, ethnicity, social class, sexuality, physical ability could all springhead restrictions of mobility which is a source of inequity. Inequity within the transport system could result in transport-related social exclusion, which means that some people are hampered from participation in the economic, social and political life when it is demanded and desired.